Theoritical aspects of Inflation - Berdiyev G‘ayrat Ibragimovich; Eshbekov Alisher (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
In economics, inflation is a general increase in the prices of goods and services in an economy. When the general price level rises, each unit of currency buys fewer goods and services; consequently, inflation corresponds to a reduction in the purchasing power of money. The opposite of inflation is deflation, a sustained decrease in the general price level of goods and services. The common measure of inflation is the inflation rate, the annualized percentage change in a general price index. As prices do not all increase at the same rate, the consumer price index (CPI) is often used for this purpose. The employment cost index is also used for wages in the United States.